If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2+3x-650=0
We add all the numbers together, and all the variables
x^2+3x-650=0
a = 1; b = 3; c = -650;
Δ = b2-4ac
Δ = 32-4·1·(-650)
Δ = 2609
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-\sqrt{2609}}{2*1}=\frac{-3-\sqrt{2609}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+\sqrt{2609}}{2*1}=\frac{-3+\sqrt{2609}}{2} $
| 2z=9+z | | -3(x+5)=4x+5 | | (g+4)–3g=1+g | | 3y-9=13+y/4 | | 14y-2=2(7y-1) | | 2y5+8+7y+5=180 | | 8x+3=-3x+14 | | 12y-32=41(3y-8) | | −3(h−6)=5(2h+3) | | 10x=54+3(99-x) | | -21=12-6y | | 2((4w-1)=-10(w-3)+4 | | 6x=40-12x | | -13=1/7z | | 14y-8y+2=20 | | x+1+2x-3=180 | | 25+8+7y+5=180 | | 3z=4=40 | | y/2+14=-1 | | 6(n-4)=5n | | -6.5k+0.63=-1.97 | | -200=25s | | 6x+6=6(x+2) | | 2^(x^2)*2^4=32 | | 3/4x=5-3/2x | | 0.07(7t-2)=0.49(t-5)+2.31 | | -18=-5b+7 | | 9x-1=10x+10 | | 3X=65x= | | -2+c/4=3 | | 2x+15=21x+x+5 | | -87=6x+3(1-7x) |